Linguistic Dominance and Translanguaging: Language Issues in Generations: The Legacy - Aiseng, Kealeboga (Frontiers in Communication, 2022)
The use of language(s) in media is very important as it can determine inclusion or exclusion. As such, the use of language in the media is ideological. This paper traces two contending language ideologies: linguistic dominance and translanguaging in one of the SABC’s longest-running soap operas, Generations: The Legacy. With the use of transcription data analysis and audio-visual analysis, the current study has concluded that there are issues of linguistic dominance and translanguaging in Generations: The Legacy. These language ideologies are perpetuated through the narrative and characters of the story. Focusing on the dialogues of the soap using selected episodes as case studies for analysis, the study has also concluded that creative decisions made in the soap are ideological. These findings raise questions about the use of media to perpetuate certain language ideologies and raise questions about whose interests are served by these language ideologies. The appropriate theoretical framework for this paper is the use of language in popular culture, with the view that the use of languages in popular culture can exclude and include, can empower, and disempower.